A comparative study for collocated and non-collocated sensor/actuator placement in vibration control of a maneuvering flexible satellite. (June 2015) - Shahravi, Morteza; Azimi, Milad
This paper presents a study concerning the vibration control of smart flexible sub-structures of satellite during attitude maneuver. A comparison between the collocated and non-collocated piezoceramic patches acting as sensors and actuators is performed in order to investigate their effectiveness to suppress vibrations in flexible substructures. A rigid hub with two elastic appendages containing surface bounded piezoelectric patches is being considered as satellite model. Finite element method and Lagrangian formulation are used for derivation of system equations of motion. Stability proof of the overall closed-loop system is given via Lyapunov analysis. The numerical simulations verify the results of the study.